Urinary extracellular vesicles carry multiple activators and regulators of coagulation - Saraswat, Mayank; Przybyla, Beata; Joenvaara, Sakari; Tohmola, Tiialotta; Strandin, Tomas; Puhka, Maija; Jouppila, Annukka; Lassila, Riitta; Renkonen, Risto (Frontiers in Cell and Developmental Biology, 2022)
Cells shape their extracellular milieu by secreting intracellular products into the environment including extracellular vesicles which are lipid-bilayer limited membrane particles. These vesicles carry out a range of functions, including regulation of coagulation, via multiple contributor mechanisms. Urinary extracellular vesicles are secreted by various cells, lining the urinary space, including the nephron and bladder. They are known to have procoagulant properties, however, the details of this function, beyond tissue factor are not well known. The aim of the study was to access the role of urinary extracellular vesicles in impacting coagulation upon supplementation to plasma. This could indicate their physiological function upon kidney injury or pathology. Supplementation to standard human plasma and plasmas deficient in various coagulation factors was used for this purpose, and calibrated automated thrombogram (CAT®) was the major technique applied. We found that these vesicles contain multiple coagulation-related factors, and their lipid composition affects coagulation activities of plasma upon supplementation. Remarkably, these vesicles can restore thrombin generation in FVII, FVIII, FIX and FXI -deficient plasmas. This study explores the multiple roles of urinary extracellular vesicles in coagulation in in-vitro blood coagulation and implies their importance in its regulation by several mechanisms.